APPARATUS FOR APPLYING AN ELECTRICAL SIGNAL TO A SUBJECT - IRONI, Alon; JASHEK, Ronen (2018)
An apparatus is described including placing a set of two or more electrodes (22) in electrical contact with a portion of a subject's body. At least one computer processor (24) drives the electrodes to apply an amplitude shift keying signal to the portion of the subject's body, the amplitude shift keying signal containing a high frequency component that acts as a carrier wave, the high frequency component having a frequency of between 80 Hz and 120 Hz, and a low frequency component that acts as a modulating component that modulates the carrier wave, the low frequency component having a frequency of between 1 Hz and 8 Hz. Other applications are also described. L'invention concerne un appareil impliquant la mise en contact électrique d'un ensemble d'au moins deux électrodes (22) avec une partie du corps d'un sujet. Au moins un processeur informatique (24) fait appliquer par les électrodes un signal de modulation par déplacement d'amplitude à ladite partie du corps du sujet, le signal de modulation par déplacement d'amplitude contenant une composante haute fréquence qui agit en tant qu'onde porteuse, la composante haute fréquence ayant une fréquence comprise entre 80 Hz et 120 Hz, et une composante basse fréquence qui agit en tant que composante de modulation qui module l'onde porteuse, la composante basse fréquence ayant une fréquence comprise entre 1 Hz et 8 Hz. D'autres applications sont également décrites.